DIABETES MELLITUS WITH CLINICAL PHENOTYPE OF TYPE 2 PATIENTS WITH NORMAL BODY WEIGHT - Парцхаладзе В. І.,; Гончарова О. А.,; Ільїна І. М., (World of Medicine and Biology, 2014)
Based on the study of autoantibodies to GAD and ICA in 126 patients with an initial diagnosis of type 2 diabetes LADA set to 16.7%, with almost the same frequency in the subgroups with normal, overweight and obese. In patients with normal body weight in the absence of significant differences in age at the time of the debut of diabetes and duration of the disease was characterized by LADA trend towards greater frequency of hypertension and type 2 diabetes - a frequent pronounced increase in waist circumference and hypertriglyceridemia, which may indicate the heterogeneity of their cardiac risk.
Keywords: type 2 diabetes; cardiac risk factors